The adverse events of CDK4/6 inhibitors for HR+/ HER2- breast cancer: an umbrella review of meta-analyses of randomized controlled trials - Pu, Dongqing; Wu, Yue; Xu, Debo; Shi, Guangxi; Chen, Hanhan; Feng, Dandan; Zhang, Mengdi; Li, Jingwei (Frontiers in Pharmacology, 2024)
Background: The clinical selection of three CDK4/6 inhibitors presents a challenging issue, owing to the absence of distinct clinical case characteristics, biomarkers, and their comparable clinical benefits in progression-free survival (PFS) and overall survival (OS). To inform clinical treatment decisions, we conducted a comprehensive evaluation of the adverse events (AEs) associated with CDK4/6 inhibitors in combination with endocrine therapy (ET) for HR+/ HER2- breast cancer. Methods: We searched Cochrane, PubMed, Embase, and Web of Science databases from their inception until August 1st, 2022. The results were summarized narratively, and we assessed the methodological quality, reporting quality, and evidence quality of AEs by AMSTAR-2, PRISMA, and GRADE. Results: Our analysis included 24 meta-analyses (MAs)/systematic reviews (SRs) that evaluated the quality of AEs in 13 cases of early breast cancer (EBC) and 158 cases of advanced breast cancer (ABC). The addition of CDK4/6 inhibitors was found to significantly increase AEs of any grade and AEs of grade 3 or higher in EBC, along with a significant increase in the risk of treatment discontinuation. In advanced breast cancer, high and moderate-quality evidence indicated that CDK4/6 inhibitors significantly increased AEs across all grades, including grade 3/4 AEs, leucopenia, grade 3/4 leucopenia, neutropenia, grade 3/4 neutropenia, anemia, grade 3/4 anemia, nausea, grade 3/4 constipation, fatigue, pyrexia, venous thromboembolism (VTE), abdominal pain, and cough. However, they did not significantly elevate the incidence of grade 3/4 diarrhea. Subgroup analysis revealed that palbociclib primarily increased hematologic toxicity, particularly grade 3/4 neutropenia, anemia, and thrombocytopenia. Ribociclib was mainly associated with grade 3/4 neutropenia, prolonged QT interval, and alopecia. Abemaciclib was closely linked with diarrhea and elevated blood creatinine levels. Conclusions: The AEs associated with CDK4/6 inhibitors vary, necessitating individualized and precise clinical selection for optimal management. This approach should be based on the patient's medical history and the distinct characteristics of different CDK4/6 inhibitors to improve the patient's quality of life.